Multisite Infections Caused by Carbapenem-Resistant Klebsiella Pneumoniae: Unveiling the Clinical Characteristics and Risk Factors - Jing Li; Shunjun Wu; Huanhuan Zhang; Xingxing Guo; Wanting Meng; Heng Zhao; Liqiang Song (Antibiotics)
Objectives: There is a scarcity of studies on multisite infections (MSIs) caused by carbapenem-resistant Klebsiella pneumoniae (CRKP). The primary objectives of this research were to determine the clinical characteristics of CRKP MSI, and the risk factors of infection and mortality. Methods: Patients with a CRKP bloodstream infection (BSI) were enrolled retrospectively between January 2017 and December 2021 in Xijing Hospital, China. The risk factors for CRKP MSI and mortality were evaluated. The demographic data, clinical and microbiological characteristics, therapy and outcomes were analyzed. Results: Among 101 patients, 74.3% (75/101) had a diagnosis of CRKP MSI, while 25.7% (26/101) of CRKP non-MSI. The overall case fatality rate was 42.6% (43/101). Multivariate analysis indicated that previous surgery (OR 3.971, 95% CI 1.504–10.480, p = 0.005) and ICU admission (OR 3.322, 95% CI 1.252–8.816, p = 0.016) were independent risk factors for CRKP MSI. ICU admission (OR 4.765, 95% CI 1.192–19.054, p = 0.027), a Pitt bacteremia score (PBS) > 4 (OR 3.820, 95% CI 1.218–11.983, p = 0.022) and thrombocytopenia (OR 8.650, 95% CI 2.573–29.007, p < 0.001) were independent risk factors for mortality due to CRKP MSI. Conclusions: Our findings confirmed that CRKP MSIs were associated with poorer outcomes. To improve prognosis, early screening of individuals at the highest risk is vital.